MARILLION’S CLUTCHING AT STRAWS: A NARRATOLOGICAL ANALYSIS - da Silva Cortez, Alexandre (Revista Gênero e Interdisciplinaridade, 2024)
This research provides a comprehensive and interpretative narratological analysis of the album “Clutching at Straws” released by the British progressive rock band Marillion in 1987. It explores the lyrical narrative, central themes, musicality, and structure of the album, as well as the historical, emotional, and artistic context of the band at the time the work was recorded and released. To achieve this, we draw upon the theoretical framework of authors such as Herman (2009), Genette (1972,1997), Reuter (2002), Bakhtin (1975), and Graudeault (2004). We believe that the narrative depth and emotional charge of the album make it a captivating topic for narratological analysis, offering a possibility for investigation into the power of narrative in the musicological context.